ANALYSIS OF ABUSE OF AUTHORITY RESULTING IN CRIMINAL ACTS OF CORRUPTION - Baharuddin Badaru (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2020)
Many officials abuse their authority, resulting in criminal acts of corruption that harm state finances. In this way, corruption has become a tradition for state officials, resulting in the eradication of corruption being somewhat difficult to eradicate because corruption is carried out in an organized manner or in groups such as that carried out by members of the People's Representative Council both at the center and in the regions.